Quality in the administration of inotropic medications in nursing professionals of a hospital in Tabasco, Mexico - Ruíz Rosado, Adriana (2020)
The aim was to evaluate the quality in the administration of inotropic medications in the nursing staff of a high specialty hospital in Tabasco, Mexico. It is an observational, cross-sectional, analytical study. A sample was obtained for the convenience of 80 nursing professionals. To assess the knowledge, the quality and safety questionnaire of the administration of inotropic medications from Ipanaque and Pérez was used. Compliance with quality standards was evaluated with the official drug administration card of the National System of Health Quality Indicators in Mexico. For data analysis, descriptive and analytical statistics were used, SPSS Version 22.0 was used. The level of quality in the administration of inotropics in the hospital evaluated was insufficient in 73.8% (59). The nurses in the intensive care service were the best evaluated in 66% with an X2 of 20,622 and a statistically significant value of p = .002. Unlike nurses in the emergency department who reached the lowest level of quality in 27.1% of them. Conclusions: the level of quality and safety in the administration of inotropics was insufficient. Constant supervision and training is suggested at the critical points found to avoid adverse events and ensure patient safety.